Hand-based biometrics : methods and technology - Drahanský, Martin (IET security series, 2018)
Hand-based biometrics identifies users by unique features in their hands, such as fingerprints, palmprints, hand geometry, and finger and palm vein patterns. This book explores the range of technologies and methods under development and in use for hand-based biometrics, with evaluations of the advantages and performance of each.